WAYS OF MODELING DISTRIBUTED SYSTEMS WITH RANDOM EFFECTS - V. A. Nosova; I. M. Pershin; S. N. Rusak (Современная наука и инновации)
An analysis of the works of domestic and foreign scientists K.G. Valeev and O.A. Zhautykov showed that finite-dimensional approximation methods are often used to solve problems of analysis and synthesis of distributed systems.